THE USE OF ICT IN RELATION TO THE PARAGRAPH WRITING ACHIEVEMENT OF ENGLISH EDUCATION STUDY PROGRAM STUDENTS AT SRIWIJAYA UNIVERSITY - Simamora, Melisa Kristina; Inderawati, Rita; Hayati, Rita (English Community Journal, 2020)
Technology has spread throughout the world and has been used by the world community in the 21st century era. The use of technology is integrated into almost all aspects of human life, including education in paragraph writing. The objective of this study was to find out whether or not there was any significant correlation between the use of ICT and paragraph writing achievement. The sample of this study was 75 fourth-semester students of English Education Study Program at Sriwijaya University. The sampling technique used was total sampling method. In collecting the data, two kinds of instruments, the use of ICT tools questionnaire and paragraph writing achievement were used. The Pearson Product Moment Correlation Coefficient was used to analyse the data. The correlation coefficient (Pearson Correlation) was 0.591, it means the degree of the correlation was fair correlation and the result of Pearson Product Moment Correlation Coefficient showed that there was a significant correlation between the use of ICT and paragraph writing achievement because p-value (0.000) was lower than (0.05).